2018
DOI: 10.1002/mmce.21283
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized dual-band metamaterial inspired antenna with modified SRR loading

Abstract: A miniaturized dual‐band CPW‐fed Metamaterial antenna with modified split ring resonator (SRR) loading has been presented in this paper. Proposed antenna comprises a tapered rectangular patch with a slot in which an elliptically SRR has been loaded to achieve miniaturization. Proposed antenna shows dual band operations in the operating band 3.25‐3.42 and 3.83‐6.63 GHz, respectively. It has been observed that lower mode (at 3.36 GHz) is originated by means of modified SRR. SRR is being modified by small meander… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…This reduction in operating frequency without increasing the antenna footprint is described as antenna miniaturization. The realized frequency reduction and hence the miniaturization is higher than the antennas reported in References 13‐18,22‐27.…”
Section: On‐car Performance Estimationmentioning
confidence: 75%
“…This reduction in operating frequency without increasing the antenna footprint is described as antenna miniaturization. The realized frequency reduction and hence the miniaturization is higher than the antennas reported in References 13‐18,22‐27.…”
Section: On‐car Performance Estimationmentioning
confidence: 75%
“…It is an effective technique to reduce the antenna's electrical size. Though the antenna achieves size reduction, it covers 3.5/5 GHz of wireless applications only 27 . A CPW‐fed metamaterial‐inspired antenna is proposed to obtain a wider bandwidth with triple‐band operations.…”
Section: Introductionmentioning
confidence: 99%
“…However, it does cover only single frequency band. From the above literature survey, it is observed that most of the existing antenna designs have the following issues: large size, narrow bandwidth, gain, ka, and less coverage of applications 22–42 . To address the above issues, a compact antenna design with a rectangular‐shaped split‐ring resonator (RSRR) structure is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main limitations of a slot antenna is that at low microwave frequencies, the antenna size becomes quite large . Nowadays, one primary focus of wireless technology is to make the system and device compact, and in general, an antenna occupies a considerable area of a wireless system compared to other components . To cope with the system and device miniaturization trend, each component needs to be miniaturized, including the antenna.…”
Section: Introductionmentioning
confidence: 99%